The influence of executive characteristics on corporate social innovation - Himel, Shadrul Hassan (2025)
Firms can integrate innovative products or services into business strategies to solve social problems and provide economic returns through corporate social innovation (CSI). It is important for businesses to consider profits and solve social problems with their products or services to be sustainable. CSI is an emerging research area where literature suggests that different aspects of organisations can influence CSI. Though previous literature provided insights into the importance and evolution of CSI, there is a knowledge gap in theory regarding the concept and resources of CSI. It is argued that CSI is a strategic decision that requires effective resource allocation (financial, human, and organisational resources) and the capability or characteristics of a CEO (such as education, experience, tenure, social networks, and connections). These background characteristics of a CEO can be influential factors in initiating CSI as these factors are used to indicate their social skills, knowledge, or abilities. This study has given an opportunity to fill the gap and contribute to knowledge by examining the characteristics of CEOs that can influence CSI. I incorporated stakeholder theory, upper-echelon theory, social capital and human capital theory in this research to contribute to the CSI literature. These theories described why and how the differences in the individual’s ability, skills and characteristics can provide different strategic and innovative outcomes. As my research questions are related to the top management resources, skills, and abilities as well as strategic decision-making processes like CSI, the interconnection of these theories guided me to address my research questions and assist me in achieving the research objectives. I adopted a sequential mixed methodology (qualitative followed by quantitative) in my PhD thesis. I have conducted a qualitative study to identify the perception of top management regarding CSI, the role of top management in CSI, and the CEO characteristics that can influence the CSI strategic decision consecutively. To achieve these objectives, I have conducted 21 interviews with different top-level management employees and experts in the financial sector of Bangladesh as an emerging economy. I also conducted five additional interviews with top-level managers of the financial sector in Malaysia and one top-level executive from Thailand to validate my qualitative study results. The financial sector, especially banking operations, mainly assists in exploring opportunities by utilising financial resources in social development, such as education, health, and entrepreneurship, reducing income inequality, which is an essential agenda for sustainable development goals. The financial sector reflects an economy's economic functions and strength. So, the financial industry of these countries is an appropriate context for this study. I selected these countries because of their similar emerging economies and cultural proximity, which can provide the generalisability of the research. I have performed phenomenography and thematic analysis to analyse the results of my qualitative research. I have found four perspectives on CSI based on top management's perceptions. These are technological, sustainability, social development, and entrepreneurship perspectives. The qualitative results also suggest that the CEO, as a top management team member, play a vital role in embedding social innovations in corporate strategy. The top management team or CEO act as an idea generator, communicator, risk taker, and implementor of CSI. My qualitative study also unveiled the top-level management or CEO characteristics which can play a role in initiating and implementing the CSI. I found that top-level managers' or CEOs' human capital, such as experience level, education, technological knowledge, and mindset, play critical roles in influencing CSI as strategic decisions. Moreover, as a source of social capital, the CEO's social network with non-profit organisations, other boards and government organisations can influence CSI. The results also suggest that CEO empathy as social capital can influence the CSI strategic decisions in the organisations. For the quantitative part, I collected data from different sources of databases (Fitch connect, Orbis bank focus), annual reports, and companies' websites. This is the unique hand-collected dataset from which I examined the extent to which CEO characteristics influence CSI. There are 45 Bangladeshi banks, 19 Malaysian banks, and 8 Thai banks included in my observation. I have collected data from 2008 to 2020 to prepare the panel data set of 823 observations. I have used a negative binomial regression model as my dependent variable is count. I have compared Akaike's information criterion (AIC) and Bayesian information criterion (BIC) between different models to justify appropriate regression model selection. I also conducted a comparison test through the mean and variance of CSI (dependent variable). I have also done the overdispersion test to select an appropriate regression model. These test results suggested using negative binomial regression as an appropriate model for my data analysis. I confirmed the results from the negative binomial models held using alternative, albeit less optimal model specifications (Poisson and OLS). My quantitative study reveals that CEO overseas education and experience level positively influence CSI, and CEO tenure negatively influences CSI. CEO overseas education positively moderates the relationships between CEO experience and CSI. Similarly, CEO overseas education positively moderates CEO tenure and CSI relationships. I also incorporated bank size (company size) as an organisational factor to investigate its effect on CSI. The study results suggest that company size positively moderates the relationship between CEO tenure and CSI. The results also suggest that CEO affiliation with non-profit organisations negatively influences the CSI. My research will contribute to corporate social innovation, sustainability, and responsible and ethical business literature. The managerial implication of my research contributes to the recruitment and selection of appropriate CEO and TMT members to compose efficient top management to initiate and implement the CSI.